Evaluation of anti-oxidant status in-vitro and in-vivo in hydro-alcoholic extract of Eugenia caryophyllus - Ghai, Roma; Nagarajan, Kandasamy; Singh, Jitendra; Swarup, Shiwam; Keshari, Minu (International Journal of Pharmacology and Toxicology, 2016)
Free radicals mediated oxidative stress is the major risk factor for many chronic diseases like atherosclerosis, diabetes mellitus, arthritis, cancer, ageing and neurodegenerative diseases. Therapy with anti-oxidants is gradually gaining lot of importance for treatment of such diseases. Hydro-alcoholic extract of Eugenia caryophyllus was studied for its in-vivo antioxidant activity using two different animal models viz. Triton induced hyperlipidemia and High fat diet induced hyperlipidemia. Total phenolic content and total flavonoid content, DPPH assay was also carried out for in vitro anti-oxidant efficacy. Total protein, lipid peroxidation (MDA), reduced glutathione, superoxide dismutase and catalase were evaluated in the liver tissue in Triton induced hyperlipidemia and diet induced hyperlipidemia models. The study findings indicated significant in-vivo and in-vitro antioxidant property that may be related to the amount of polyphenols and flavonoids present in the extract. These results clearly indicate that Eugenia caryophyllus is effective against free radical mediated oxidative stress.